Improving new technology venture performance under direct and indirect network externality conditions - Podoynitsyna, Ksenia; Song, Michael; van der Bij, Hans; Weggeman, Mathieu (Journal of Business Venturing, 2013)
This study compares the effectiveness of five responses to external uncertainty in markets with network externalities: avoidance, imitation, control, cooperation, and real options reasoning as a form of strategic flexibility. Our analysis of 385 new technology ventures shows that direct and indirect network externalities have opposite effects on the effectiveness of these strategies. Moreover, under network externalities, attempts to make ventures less dependent upon environmental instabilities perform differently compared to attempts to control the environment. Finally, we show that real options reasoning does not always perform better under conditions of higher uncertainty, such as uncertainty due to direct network externalities.